Transportation carbon emission efficiency network formation mechanism and spatial structural complexity analysis: Evidence from China - Lin Liu; Yuming Liu; Rong Zhao (Sustainable Futures)
The growing intricacy and expansion of the transportation network structure present challenges to achieving low-carbon development and sustainable growth in China's regional transportation industry. This study employs the super-efficiency SBM model and social network analysis to examine the mechanistic formation of carbon emission networks, emphasizing temporal and gradient distribution patterns of efficiency networks, spatial transfer pathways, efficiency evolution characteristics, and the complexity of microstructures. Findings reveal: (1) The overall efficiency of carbon emissions exhibits a “N-shaped” trend over time, driven by local high efficiency inducing overall high-efficiency output. (2) Regional imbalances persist, characterized by a “λ-shaped” fixed radiation pattern centered around Beijing, with spatial transmission from eastern coastal areas to north-south transfer to western diffusion. The central region lacks a well-structured efficiency guidance system. (3) A multi-level composite network system exists among provinces, featuring a coordination network as the primary component and backbone network as secondary element. The coordination network serves as a stable driving force, enhancing efficiency network density, with increased robustness in the central and eastern regions and a closed connectivity structure in the northwest. (4) Internal node differences contribute to uneven development; nodes jointly formed with Beijing act as gatekeepers, controlling medium and high efficiency networks in the eastern, central, and northern regions. The “One super-Five strong” nodes and “Two Zones – Four Wings” alliance generate significant external connectivity, enhancing network complexity and resilience. The study proposes policy recommendations, focusing on optimizing the transportation network structure and carbon emission rights market trading to improve carbon emission efficiency.